River Jordan : African American urban life in the Ohio Valley - Trotter, Joe William, 1945- (Ohio River Valley series., 1998)
Since the nineteenth century, the Ohio River has represented a great divide for African Americans. It marked the passage to freedom along the underground railroad, and during the Industrial age it was a boundary between the Jim Crow South and the urban North. Consequently, the Ohio became known as the "River Jordan," symbolizing the path to the promised land. Beginning with the arrival of the first blacks in the Ohio Valley, Trotter traces the development of African American urban centers through the civil rights movement. River Jordan broadens our understanding of the black experience in the United States and illuminates the impact of the Ohio River in the context of the larger American story.